Toll - Shusterman, Neal (New York Simon & Schuster BFYR, 2019)
In the finale to the Arc of a Scythe trilogy, dictators, prophets, and tensions rise. In a world that's conquered death, will humanity finally be torn asunder by the immortal beings it created? Citra and Rowan have disappeared. Endura is gone. It seems like nothing stands between Scythe Goddard and absolute dominion over the world scythedom. With the silence of the Thunderhead and the reverberations of the Great Resonance still shaking the earth to its core, the question remains: Is there anyone left who can stop him? The answer lies in the Tone, the Toll, and the Thunder.--adapted from publisher's description.
Ages 12 up.
Grades 7-9.
107522
Keywords: Immortality -- Fiction; Dystopias; Death; Murder; Science fiction; Social Themes -- Death, Grief, Bereavement; Action & Adventure -- General; Young adult fiction; Fiction; Science fiction; Novels